Livestock losses and post-drought rehabilitation in sub-Saharan Africa - Toulmin, C. (International Livestock Centre for Africa, 1985)
Examines post-drought rehabilitation policies to aid recovery in livestock production and crop production, and the effects of drought on livestock and farming communities. Discusses the role played by reserves in mitigating a population's vulnerability to drought; and the macro-economic implications of a drought induced loss of livestock for the government budget, domestic markets and external trade. Investigates the likely speed of recovery in the abscence of outside intervention. Presents materials from case studies to show the nature of costs and returns involved. Suggests priority areas for action for decision makers.